Heart Rate Fragmentation: A Symbolic Dynamical Approach - Costa, Madalena D.; Davis, Roger B.; Goldberger, Ary L. (Frontiers in Physiology, 2017)
Background: We recently introduced the concept of heart rate fragmentation along with a set of metrics for its quantification. The term was coined to refer to an increase in the percentage of reversals in heart rate acceleration sign, a dynamical marker of a type of anomalous variability. The effort was motivated by the observation that fragmentation, which is consistent with the breakdown of the neuroautonomic-electrophysiologic control system of the sino-atrial node, could confound traditional short-term analysis of heart rate variability. Objective: The objectives of this study were to: 1) introduce a symbolic dynamical approach to the problem of quantifying heart rate fragmentation; 2) evaluate how the distribution of the different dynamical patterns (``words'') varied with the participants' age in a group of patients with coronary artery disease (CAD) and in healthy subjects; 3) quantify the differences in the fragmentation patterns between the two sample populations. Methods: The symbolic dynamical method employed here was based on a ternary map of the increment NN time series and on the analysis of the relative frequency of symbolic sequences (words) with a pre-defined set of features. We analyzed annotated, open-access Holter databases of healthy subjects and patients CAD, provided by the University of Rochester Telemetric and Holter ECG Warehouse (THEW). Results: The degree of fragmentation was significantly higher in older individuals than in their younger counterparts. However, the fragmentation patterns were different in the two sample populations. In healthy subjects, older age was significantly associated with a higher percentage of transitions from acceleration/deceleration to zero acceleration and vice versa (termed ``soft'' inflection points). In patients with CAD, older age was also significantly associated with higher percentages of reversals in heart rate acceleration (transitions from acceleration to deceleration and vice versa, termed ``hard'' inflection points). Compared to healthy subjects, patients with CAD had significantly more soft and hard inflection points, more words with a high degree of fragmentation and fewer words with a lower degree of fragmentation. Conclusion: The symbolic dynamical method used here was useful to probe the newly recognized property of heart rate fragmentation. The findings from these cross-sectional studies confirm that CAD